Spatially Programmable Architected Materials Inspired by the Metallurgical Phase Engineering - Liu, Chen (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.